PENGARUH WORK FROM HOME (WFH) DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DENGAN KOMUNIKASI INTERPERSONAL SEBAGAI VARIABEL INTERVENING: Studi Pada Balai Pengkajian Teknologi Pertanian Provinsi Banten - Sofiea Nisa Assyami; Moh Mukhsin; Liza Mumtazah Damarulan (Universitas Methodist Indonesia, 2022)
Work from home has become a growing concern for employers and employees in most organizations with a flexible work environment, flexibility to work, freedom of time, using information and communication technology. Work discipline is related to compliance with applicable regulations, responsibilities in carrying out tasks, carrying out work tasks to completion every day, timeliness of arrival until completion of meetings/discussions, closely related to employee performance related to quality, quantity, timeliness and productivity. Coupled with interpersonal communication related to Openness, Empathy, Support, Equality. The purpose of this study was to determine and analyze the effect of Work from home (WFH) and Work Discipline on Employee Performance with Interpersonal Communication as an Intervening Variable, at the Center for the Assessment of Agricultural Technology, Banten Province. The methodology used is a survey design, using a quantitative descriptive method with a sample of 80 respondents with an interval measurement scale of 1-10 and analyzed using the Smart PLS 3.29 application. The results of this study indicate that there is a significant influence between: 1. Work from home (WFH) has an effect on Performance, 2. Work Discipline has an effect on Employee Performance, 3. Work from home (WFH) has an effect on Interpersonal Communication, 4. Work Discipline has an effect on Interpersonal Communication, 5. Interpersonal Communication has a Simultaneous effect on Employee Performance, with the results of the independent variable and the dependent variable being strengthened by the influence of the intervening variable. This study therefore rejects all null hypotheses because the estimates are statistically significant.